Allergen Recognition in Food Ingredients with Computer Vision - Elisa Belinda Johan; Aminuddin Rizal (Ultima Computing : Jurnal Sistem Komputer, 2021)
The process of recognition and classification of food is very important. It can be useful for consumers who are sensitive in choosing foods that they want to consume. Considering that some food ingredients are allergens that can cause allergies for some people. This paper aims to design and build an Android-based system to detect food ingredients that can facilitate consumers in getting information about all allergens contained in the. The application is created by implementing Optical Character Recognition (OCR) algorithm and using Boyer Moore algorithm to do the word matching (string matching). The experiments were performed with trial of OCR, Boyer Moore, light sources, and technical words (uncommon words). Our experiment shows more than 90% accuracy obtained with different scenario applied.